STUDI KOMPARATIF TENTANG MAHAR HAFALAN AL-QUR’AN DI KALANGAN MUDA MENURUT MADZHAB SYAFI’I DAN MADZHAB HANAFI - M.Fakhrurrozi Zulsa Matondang; Ali Akbar (LP2M IAI Nazhatut Thullab Sampang, 2023)
Abstract: The large number of millennials today who adopt the habit of giving memorization of the Qur'an as a wedding dowry is a social phenomenon that attracts attention. These gifts are often not based on an understanding of Islamic law or jurisprudence, but rather influenced by personal motivation, ease of execution, and other external factors. The memorization of the Qur'an as a form of marriage dowry, when analyzed through the perspective of the two madhhabs, namely the Shafi'i madhhab and the Hanafi Muta'akhirin madhhab, shows that this practice is still legally acceptable and as long as it does not contradict the teachings of Islam. The approach to the form of dowry in the form of merit has differences between Shafi'i Madzhab and Hanafi Madzhab. The Shafi'i Madhhab allows the use of dowry in the form of services, because there is no minimum limit required in giving dowry. Anything that has beneficial value, such as the teaching of the Qur'an and religious knowledge, sewing skills, strengthening Islam, and even the liberation of slaves, are all considered valid dowries. On the other hand, the Hanafi Madhhab stipulates that the minimum limit for giving dowry is ten dirhams. For this reason, dowry in the form of merit is not recognized, because it is considered to have a value of less than ten dirhams. In addition, giving remuneration for the teaching of the Qur'an and religious knowledge is considered by the Hanafi Madhhab as an act aimed at achieving piety to Allah Almighty, so providing financial compensation is considered inappropriate. Thus, the phenomenon of giving memorization of the Qur'an as a marriage dowry from the point of view of Islamic law is still open, and the perspectives of the Shafi'i Madhhab and the Hanafi Madzhab provide different views regarding the form of dowry in the form of merit, depending on the interpretation and approach followed. Keywords: Dowry, Qur'an Memorization, Comparative, Young people Abstrak: Banyaknya generasi milenial saat ini yang mengadopsi kebiasaan memberikan hafalan Al-Qur'an sebagai mahar pernikahan merupakan fenomena sosial yang menarik perhatian. Pemberian ini seringkali tidak didasarkan pada pemahaman hukum Islam atau fikih munakahat, melainkan lebih dipengaruhi oleh motivasi pribadi, kemudahan dalam melaksanakan, serta faktor-faktor eksternal lainnya. Hafalan Al-Qur'an sebagai bentuk mahar pernikahan, ketika dianalisis melalui perspektif kedua madzhab yaitu madzhab Syafi’i dan Madzhab Hanafi Muta’akhirin, menunjukkan bahwa praktik ini masih dapat diterima secara hukum dan selagi tidak bertentangan dengan ajaran Islam. Pendekatan terhadap bentuk mahar berbentuk jasa memiliki perbedaan antara Madzhab Syafi'i dan Madzhab Hanafi. Madzhab Syafi'i memperbolehkan penggunaan mahar berupa jasa, sebab tidak ada batasan minimal yang diharuskan dalam memberikan mahar. Apapun yang memiliki nilai bermanfaat, seperti pengajaran Al-Qur'an dan ilmu agama, keterampilan menjahit, penguatan keislaman, dan bahkan pembebasan budak, semuanya dianggap sebagai mahar yang sah.Di sisi lain, Madzhab Hanafi mengatur bahwa batas minimal pemberian mahar adalah sepuluh dirham. Karena alasan ini, mahar berupa jasa tidak diakui, karena dianggap memiliki nilai kurang dari sepuluh dirham. Selain itu, memberikan upah atas pengajaran Al-Qur'an dan ilmu agama dianggap oleh Madzhab Hanafi sebagai tindakan yang bertujuan mencapai ketakwaan kepada Allah SWT, sehingga memberikan kompensasi finansial dianggap tidak pantas.Dengan demikian, fenomena memberikan hafalan Al-Qur'an sebagai mahar pernikahan dari sudut pandang hukum Islam masih bersifat terbuka, dan perspektif Madzhab Syafi'i dan Madzhab Hanafi memberikan pandangan yang berbeda terkait bentuk mahar berbentuk jasa, tergantung pada interpretasi dan pendekatan yang diikuti. Kata Kunci: Mahar, Hafalan Qur’an, Komparatif, Kalangan Muda